Median eminence myelin continuously turns over in adult mice - Sophie Buller; Sara Kohnke; Robert Hansford; Takahiro Shimizu; William D. Richardson; Clemence Blouet (Elsevier, 2023)
Objective: Oligodendrocyte progenitor cell differentiation is regulated by nutritional signals in the adult median eminence (ME), but the consequences on local myelination are unknown. The aim of this study was to characterize myelin plasticity in the ME of adult mice in health or in response to chronic nutritional challenge and determine its relevance to the regulation of energy balance. Methods: We assessed new oligodendrocyte (OL) and myelin generation and stability in the ME of healthy adult male mice using bromodeoxyuridine labelling and genetic fate mapping tools. We evaluated the contribution of microglia to ME myelin plasticity in PLX5622-treated C57BL/6J mice and in Pdgfra-Cre/ERT2;R26R-eYFP;Myrffl/fl mice, where adult oligodendrogenesis is blunted. Next, we investigated how high-fat feeding or caloric restriction impact ME OL lineage progression and myelination. Finally, we characterized the functional relevance of adult oligodendrogenesis on energy balance regulation. Results: We show that myelinating OLs are continuously and rapidly generated in the adult ME. Paradoxically, OL number and myelin amounts remain remarkably stable in the adult ME. In fact, the high rate of new OL and myelin generation in the ME is offset by continuous turnover of both. We show that microglia are required for continuous OL and myelin production, and that ME myelin plasticity regulates the recruitment of local immune cells. Finally, we provide evidence that ME myelination is regulated by the body's energetic status and demonstrate that ME OL and myelin plasticity are required for the regulation of energy balance and hypothalamic leptin sensitivity. Conclusions: This study identifies a new mechanism modulating leptin sensitivity and the central control of energy balance and uncovers a previously unappreciated form of structural plasticity in the ME.